(3QSGdI OGFQI JhUjI ddeTjNI hGdONhd aj GdNdhIs
(3ChdgG (B:s
(3hGYde Cf ZGdH eQjOj gPG GdReGf de jUQ YfOge GdBf geI s
(3BNQgG (B:s
(3hdcf GdTHGH EPG Jhdi Ydi TQa aeWdHg HYjO JeJ GdQSGdI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3GdehUd (B(448) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs